Testing and Validating an Ideal Work Practice Model for Distance Learning Taxation Students: An Industry Collaboration Approach - Syafiqoh Nurhayati; Dedy Juniadi; Erman Arif (UNIVED Press, 2025)
This research aims to test and validate the ideal work practice model for Universitas Terbuka Taxation students through collaboration with industry partners. The research method used a mixed approach, involving 100 students and 20 industry partners. Data was collected through pre-test and post-test competency, partner questionnaires, and student reflective reports. The results of the statistical test showed a significant increase in student competence, with the average pre-test score of 64.2 and the post-test increased to 83.7 (p < 0.01). Qualitative analysis from 20 industry partners indicates a satisfaction rate of 92% with student job readiness. In addition, 87% of students feel that the work practice model provides real and relevant experience. These results demonstrate the effectiveness of the model in improving the career readiness and quality of vocational graduates in a distance learning environment. This model is recommended to be widely applied with adjustment of local context and industry needs